A novel multielement nanocomposite with ultrahigh rate capacity and durable performance for sodium-ion battery anodes. Issue 23 (8th June 2020) - Ren, Xiaochuan; Zhao, Yuanxin; Li, Qingwei; Cheng, Feng; Wen, Wen; Zhang, Lili; Huang, Yaobo; Xia, Xinhui; Li, Xiaolong; Zhu, Daming; Huo, Kaifu; Tai, Renzhong
Abstract : Novel multielement SnPSe3 @graphene with good synergistic reversibility induces enhanced sodium storage activity, cycling stability and high initial coulombic efficiency. Abstract : Tin (Sn) and phosphorus (P) have been recognized as promising anode materials for high-energy sodium-ion batteries (SIBs) due to their low cost and high theoretical capacity. However, the respective shortcomings of Sn- or P-based sodiation phases, such as low conductivity and large volume change, seriously deteriorate their cycle life and rate capabilities. Herein, for the first time, we have reported a novel multielement SnPSe3 @graphene nanocomposite (SnPSe3 @G) with outstanding Na-ion storage performance. Its intrinsically good conductivity and the synergistic effect of complementary elements make up for the shortcomings of a single element, enabling fast charge transport kinetics and high structural integrity, which result in prolonged cycling stability and high rate capability. The SnPSe3 @G anode exhibits a large capacity of 823 mA h g −1 at 100 mA g −1 with a high initial coulombic efficiency (CE) of 95%, excellent rate performance (362 mA h g −1 at 10 A g −1 ), and extraordinary ultra-long cycle life (79% capacity retention after 4000 cycles at 10 A g −1 ). When further combined with an Na3 V2 (PO4 )3 /C cathode, the resulting Na-ion full cell exhibits a high energy density of 126.2 W h kg −1 and good cycling stability. This exceptional performance indicates the application potential of multielement synergistic anodes in sodium-ion batteries.